Charles S. Peirce On Norms and Ideals - Potter, Vincent G. (Fordham University Press, 2019)
In recent years, Charles Sanders Peirce has emerged, in the eyes of philosophers both in America and abroad, as one of America's major philosophical thinkers. His work has forced us back to philosophical reflection about those basic issues that inevitably confront us as human beings, especially in an age of science. Peirce's concern for experience, for what is actually encountered, means that his philosophy, even in its most technical aspects, forms a reflective commentary on actual life and on the world in which it is lived. In Charles S. Peirce: On Norms and Ideals, Potter argues that Peirce's doctrine of the normative sciences is essential to his pragmatism. No part of Peirce's philosophy is bolder than his attempt to establish esthetics, ethics, and logic as the three normative sciences and to argue for the priority of esthetics among the trio. Logic, Potter cites, is normative because it governs thought and aims at truth; ethics is normative because it analyzes the ends to which thought should be directed; esthetics is normative and fundamental because it considers what it means to be an end of something good in itself. This study shows that pierce took seriously the trinity of normative sciences and demonstrates that these categories apply both to the conduct of man and to the workings of the cosmos. Professor Potter combines sympathetic and informed exposition with straightforward criticism and he deals in a sensible manner with the gaps and inconsistencies in Peirce's thought. His study shows that Peirce was above all a cosmological and ontological thinker, one who combined science both as a method and as result with a conception of reasonable actions to form a comprehensive theory of reality. Peirce's pragmatism, although it has to do with "action and the achievement of results, is not a glorification of action but rather a theory of the dynamic nature of things in which the "ideal" dimension of reality - laws, nature of things, tendencies, and ends - has genuine power for directing the cosmic order, including man, toward reasonable goals.